Students’ experiences of co-creating classroom instruction with faculty- a case study in eastern context - Kaur, Amrita; Awang Hashim, Rosna; Kaur, Manvender (Routledge, 2019)
In order to co-create teaching and learning for enhanced student engagement, faculty–student partnership in higher education is emerging as a distinguished practice in the West especially for undergraduates. However, little is known about the impact of such practices in the East. This article reports the benefits of a term long collaboration between the faculty and students in designing and delivering classroom instructions through the experiences of faculty–student partnership of post graduate students. The findings indicate that while students had positive experiences, they were also distinct in a number of ways when compared with the experiences of students in the West. Students also provided insightful information on the mechanism of navigating through their newly assigned roles of partnership with their faculty. The implications are discussed for higher education practitioners and recommendations are provided for further investigation to achieve better understanding of this practice.